KAJIAN TEKNIS INTEGRASI SAWIT-ITIK (STUDI KASUS DI KELOMPOK TANI TARUNA JAYA) PELAIHARI KABUPATEN TANAH LAUT - Ilmi Hidayat; Gusti Khairun Ni'mah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This study aims to determine patterns rearing of ducks are integrated with the palm oil, and know how contribution the maintenance of duck to palm plant.The method used in this research is a case study in Farmers Group Taruna Jaya Pelaihari, Tanah Laut district that maintain of ducks integrated with oil palm plantations. The results showed that rearing ducks effective on integrase with oil palms use a mixed pattern, with three segments, namely from DOD for one month in the enclosures with a dirt floor, at the age 1- 6 months duck removable to roam among oil palm trees, and when it begins to lay eggs 50% per day until late in the maintenance (+ 20 months) is raised on the stage enclosure. The results also showed that in addition to producing eggs, integrase duck with oil palm trees can be reduce maintenance costs on maintenance of oil palm, including free of weed, free of inorganic fertilizers except as much as 1.5 kg / tree / year of calcium oxida. The growth of oil palm production is better shown with a larger diameter trunk circumference and result production is higher than reared conventionally.